2013
DOI: 10.1016/j.neuron.2013.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control of Entrainment and Synchrony of the Suprachiasmatic Circadian Clock by mTOR/4E-BP1 Signaling

Abstract: SUMMARY Protein synthesis is critical for circadian clock function, but little is known on how translational regulation controls the master pacemaker in mammals, the suprachiasmatic nucleus (SCN). Here we demonstrate that the pivotal translational repressor, the eukaryotic translational initiation factor 4E binding protein 1(4E-BP1) is rhythmically regulated via the mechanistic target of rapamycin (mTOR) signaling in the SCN and preferentially represses vasoactive intestinal peptide (Vip) mRNA translation. Kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 71 publications
(108 reference statements)
6
126
1
Order By: Relevance
“…Moreover, the ERK1/2 MAPK pathway is also involved in regulating circadian rhythms in SCN and plays an important role in the clock-resetting mechanisms of mammalian circadian clock (40,44,45). Interestingly, mTOR activity also exhibits circadian variations in SCN (46) and has been reported to be crucial for regulating protein synthesis by modulating the phosphorylation of 4EBP and mRNAs with 5Ј-TOP motifs (47,48). Our results fit broadly with these studies suggesting that ERK1/2 MAPK and mTOR activity are critical for regulating translation initiation.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the ERK1/2 MAPK pathway is also involved in regulating circadian rhythms in SCN and plays an important role in the clock-resetting mechanisms of mammalian circadian clock (40,44,45). Interestingly, mTOR activity also exhibits circadian variations in SCN (46) and has been reported to be crucial for regulating protein synthesis by modulating the phosphorylation of 4EBP and mRNAs with 5Ј-TOP motifs (47,48). Our results fit broadly with these studies suggesting that ERK1/2 MAPK and mTOR activity are critical for regulating translation initiation.…”
Section: Discussionsupporting
confidence: 88%
“…Although rhythmic coordination of transcription and mRNA accumulation has been extensively studied during the last decades, rhythmic translation has been described only recently in mammals. Indeed, it has been shown that the TORC1 pathway is rhythmically activated in mouse liver (12,49), hippocampus (50), and SCN (51), influencing in this way rhythmic ribosome biogenesis (12) or light response and circadian behavior (52,53). Moreover, the circadian clock, in coordination with feeding rhythms, seems to play a modulating role in this activation (12,54,55).…”
Section: Translation Efficiency Is Regulated During the Diurnal Cyclementioning
confidence: 99%
“…Over the course of the day, transcript levels increase, accompanied by an increase in the levels of the relevant proteins. Circadian regulation of translational efficiency via mTOR and MAPK signaling cascades, converging on phosphorylation of the cap-binding protein eIF4E may facilitate this increase, such that by the end of circadian day nuclear complexes of PER and CRY suppress the activity of CLOCK and BMAL1 (Cao et al 2013). Crystal structures recently revealed that CRY1 binds to a PAS domain within CLOCK and a TAD domain within the carboxyl terminus of BMAL1 to switch off transcriptional activation by CLOCK-BMAL1 .…”
Section: A Short History Of the Mammalian Molecular Clockworkmentioning
confidence: 99%